(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Proximal tibia fractures are complex orthopedic problems that require a comprehensive approach for effective treatment. Such injuries often high energetic traumas , for example , traffic accidents and sports injuries as a result to the surface will come In this process immune of the system condition and to become inflamed answer of the fracture to finish and to the rehabilitation process impact to do possible That’s it. for , is a large number bone proximal part fractures treatment efficiency clinical and in assessment immunological indicators to study important importance profession will.